Comparative growth kinetics of Listeria monocytogenes and Salmonella enterica on dehydrated enoki and wood ear mushrooms during rehydration and storage - Salazar, Joelle K.; George, Josephina; Fay, Megan L.; Stewart, Diana S.; Ingram, David T. (Frontiers in Microbiology, 2024)
Specialty mushrooms have been implicated in foodborne illness outbreaks in the U.S. in recent years. These mushrooms are available to consumers in both their fresh and dried states. Dehydrating mushrooms is a convenient way to increase shelf life. The dehydration process results in a lowered water activity (aw) of the commodity, creating an environment where both spoilage and pathogenic bacteria cannot proliferate. Prior to food preparation and consumption, these mushrooms are typically rehydrated and possibly stored for later use which could lead to increased levels of pathogens. This study examined the survival and growth of Listeria monocytogenes and Salmonella enterica on dehydrated enoki and wood ear mushrooms during rehydration and subsequent storage. Mushrooms were heat dehydrated, inoculated at 3 log CFU/g, and rehydrated at either 5 or 25°C for 2 h. Rehydrated mushrooms were stored at 5, 10, or 25°C for up to 14 d. L. monocytogenes and S. enterica survived on enoki and wood ear mushroom types during rehydration at 5 and 25°C, with populations often <2.39 log CFU/g. During subsequent storage, no growth was observed on wood ear mushrooms, regardless of the rehydration or storage temperature, with populations remaining <2.39 log CFU/g for both pathogens. When stored at 5°C, no growth was observed for either pathogen on enoki mushrooms. During storage at 10 and 25°C, pathogen growth rates and populations after 14 d were generally significantly higher on the enoki mushrooms rehydrated at 25°C; the highest growth rate (3.56 ± 0.75 log CFU/g/d) and population (9.48 ± 0.62 log CFU/g) after 14 d for either pathogen was observed by S. enterica at 25°C storage temperature. Results indicate a marked difference in pathogen survival and proliferation on the two specialty mushrooms examined in this study and highlight the need for individual product assessments. Data can be used to assist in informing guidelines for time and temperature control for the safety of rehydrated mushrooms.